2020
DOI: 10.3389/fchem.2020.00060
|View full text |Cite
|
Sign up to set email alerts
|

Surface Dependent Dual Recognition of a G-quadruplex DNA With Neomycin-Intercalator Conjugates

Abstract: G-quadruplexes have been characterized as structures of vital importance in the cellular functioning of several life forms. They have subsequently been established to serve as a therapeutic target of several diseases including cancer, HIV, tuberculosis and malaria. In this paper, we report the binding of aminosugar-intercalator conjugates with a well-studied anti-parallel G-quadruplex derived from Oxytricha Nova G-quadruplex DNA. Of the four neomycin-intercalator conjugates studied with varying surface areas, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Moreover, stacking interactions were observed only for the smallest polycyclic ring, the anthraquinone intercalator. 143 …”
Section: Computational Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, stacking interactions were observed only for the smallest polycyclic ring, the anthraquinone intercalator. 143 …”
Section: Computational Studiesmentioning
confidence: 99%
“…The molecular modeling part of the study, performed with Vina, revealed for all the conjugates that neomycin was positioned in the wide groove with a linker extending the intercalating moieties more toward the thymine loop regions. Moreover, stacking interactions were observed only for the smallest polycyclic ring, the anthraquinone intercalator …”
Section: Computational Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the fluorescent modifications were also used in developing DNA- and RNA-based screening assays for rapid drug discovery of several classes of small-molecule binders ( Watkins et al, 2013 ; Ranjan and Arya, 2019 ). In comparison to DNA-binding studies with duplexes and triplexes, our investigations with DNA G-quadruplexes were limited with most of the binding studies with antiparallel G-quadruplex structures ( Ranjan et al, 2010 ; Ranjan et al, 2013b ; Ranjan et al, 2020 ). Detailed studies involving aminoglycoside binding to parallel G-quadruplexes remain unknown until now.…”
Section: Introductionmentioning
confidence: 99%